How do traditional masculinity ideologies and emotional competence relate to aggression and physical domestic violence in cisgender men? - Logoz, Flora; Eggenberger, Lukas; Komlenac, Nikola; Schneeberger, Michèle; Ehlert, Ulrike; Walther, Andreas (Frontiers in Psychology, 2023)
Background: Men are disproportionately often perpetrators of physical domestic violence (DV). Gender role constructs, such as traditional masculinity ideologies (TMI), are broadly accepted as an explanation for this effect. Emotional competence further constitutes an important role in TMI and the prevention of DV. However, the interactions between these constructs remains unclear. Objective: The present study aims to investigate associations of TMI with aggression, DV perpetration, and emotional competence, while also examining emotional competence as a potential moderator. Method: A sample of 428 cisgender men (Mage = 43.9 ± 15.3) from German-speaking countries in Europe completed an anonymous online survey that assessed TMI, aggression, and DV perpetration as well as alexithymia, emotion regulation, and self-compassion as indicators of emotional competence. Results: Strong TMI were associated with high levels of aggression and overall reduced emotional competence, as reflected by high levels of alexithymia, frequent use of expressive suppression, and low levels of self-compassion. Strong conformity to TMI was associated with a higher likelihood for DV perpetration when considering relevant sociodemographic covariates. Moderation analyses revealed that expressive suppression buffered the association between TMI and DV perpetration. Conclusions: Men with strong TMI report high levels of aggression and impaired emotional competence. While strong conformity to TMI was associated with more frequent perpetration of DV, higher expressive suppression seems to buffer the association between TMI and DV perpetration. The present study highlights the importance of addressing gender ideologies when working on aggression, DV perpetration and emotional competence in men.